2015
DOI: 10.1038/srep17198
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoside phosphorylation by the mineral schreibersite

Abstract: Phosphorylation of the nucleosides adenosine and uridine by the simple mixing and mild heating of aqueous solutions of the organic compounds with synthetic analogs of the meteoritic mineral schreibersite, (Fe,Ni)3P under slightly basic conditions (pH ~9) is reported. These results suggest a potential role for meteoritic phosphorus in the origin and development of early life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(102 citation statements)
references
References 29 publications
4
98
0
Order By: Relevance
“…The ppm scale is referenced to 0, being 85% H 3 PO 4 . The yield of phosphorylated product within this system is about 12% of the total dissolved P. Such a yield is higher than the yield from reactions in just water of schreibersite 22 but lower than directed reactions with condensed phosphates.…”
Section: Synthesismentioning
confidence: 68%
See 2 more Smart Citations
“…The ppm scale is referenced to 0, being 85% H 3 PO 4 . The yield of phosphorylated product within this system is about 12% of the total dissolved P. Such a yield is higher than the yield from reactions in just water of schreibersite 22 but lower than directed reactions with condensed phosphates.…”
Section: Synthesismentioning
confidence: 68%
“…Phosphorylation by schreibersite now has been demonstrated with glycerol, nucleosides, and with choline, suggesting that schreibersite is a fairly robust phosphorylation source. 21,22 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is ample time given that lab experiments show hourto-week-long timescales are sufficient to form adenosine and AMP [2,3].…”
Section: Daymentioning
confidence: 99%
“…[25] Others seek to introduce phosphate in a lower oxidation state from meteorites. [26] Others seek to alter the environment of the mineral. For example, during review of this paper, Burcar et al reported an elegant study showing phosphate release from apatite in eutectics made from water, urea, and ammonium formate.…”
Section: Nearlyallprebioticchemistryisdoneinglasswarefromthementioning
confidence: 99%